Oral and Topical Centella asiatica in Type 2 Diabetes Mellitus Patients with Dry Skin: A Three-Arm Prospective Randomized Double-Blind Controlled Trial. (26th August 2020) - Legiawati, Lili; Bramono, Kusmarinah; Indriatmi, Wresti; Yunir, Em; Setiati, Siti; Jusman, Sri Widia A.; Purwaningsih, Erni H.; Wibowo, Heri; Danarti, Retno
Abstract : Introduction . Uncontrolled diabetes mellitus (DM) is related to skin disorders, particularly dry skin. Pathogenesis of dry skin in type 2 diabetes mellitus (T2DM) rises from the chronic hyperglycemia causing an increase in advanced glycation end-products (AGEs), proinflammatory cytokines, and oxidative stress. Combination of oral and topical Centella asiatica (CA) is expected to treat dry skin in T2DM patients more effectively through decreasing N(6)-carboxymethyl-lysine (CML) and interleukin-1 α (IL-1 α ) and increasing superoxide dismutase (SOD) activity. Methods . A three-arm prospective, double-blind, randomized, controlled study was performed to evaluate the efficacy of the oral and topical CA extract in 159 T2DM patients with dry skin. The subjects were divided into the CA oral (CAo) 2 × 1.100 mg + CA topical (CAt) 1% ointment group, oral placebo (Plo) + CAt group, and Plo and topical placebo (Plt) group. Dry skin assessment was performed on day 1, 15, and 29, while evaluation of CML, IL-1 α, and SOD activity was on day 1 and 29. Result . Effectivity of CAo + CAt combination was assessed based on HbA1c and random blood glucose (RBG). In well-controlled blood glucose, on day 29, the percentage of SRRC decrement was greater in the CAo + CAt group compared to the control group (p = 0.04 ). SCap value in the CAo + CAt group was greater than that in the control group (p = 0.01 ). In the partially controlled blood glucose, increment of SOD activity in the CAo + CAt group was greater than that in the control group (p = 0.01 ). There were medium-to-strong correlation between CML with SOD ( r  = 0.58, p < 0.05 ) and IL-1 α with SOD ( r  = 0.70, p < 0.05 ) in well-controlled blood glucose. Systemic and topical adverse events were not significantly different between groups. Conclusion . CAo and CAt combination can be used to significantly improve dry skin condition through increasing SOD activity in T2DM patients with controlled blood glucose.